Sibling Rivalry in 2-4 Years Old Children: Maternal Management Based on Emotion Coaching Concept - Bernadette Cindy; Agustina Hendriati (PSIKODIMENSIA, 2020)
Sibling rivalry is a usual phenomenon in sibling relationship. Sibling rivalry refers to envy, jealousy, and competition between siblings. The birth of younger sibling causes the first child to be flustered, disturbed and experiences change in the routines; makes the first child to feel that parents do not have time for her/him anymore. The experience may result in the sibling relationship and child behavior problems, hence it should be managed. Mother has an important role in handling sibling rivalry and emotion coaching is one of the ways to support emotional development. Emotion coaching refers to acceptance of the emotion and teach the child to regulate it. This qualitative study explored maternal management in sibling rivalry based on emotion coaching concept. We inteviewed four mothers with two children of same sex, the first child is 2-4 years old and the second child is 0-6 weeks old. Findings revealed that the four mothers haven’t used all stages of emotion coaching in handling sibling rivalry as yet. Mothers tended to deny their child’s emotion and use their own perception in dealing with sibling rivalry. Implication of this result was discussed.